1990
DOI: 10.1002/1097-0142(19901201)66:11<2286::aid-cncr2820661106>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose preoperative radiation postpones recurrences in operable rectal cancer: Results of a randomized multicenter trial in western norway

Abstract: A randomized, multicenter clinical trial was conducted in Western Norway to study the effectiveness of preoperative radiation therapy in operable rectal cancer, given at a dosage of 3150 cGy in 18 fractions, 2 to 3 weeks before radical surgery. Three hundred nine patients were entered into the trial between May 1976 and December 1985. After radiation no tumor was seen in 4.5% of the patients. There was no increased morbidity or mortality at surgery. The 5-year survival for evaluable patients was 57.5% in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
4

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(54 citation statements)
references
References 42 publications
2
46
1
4
Order By: Relevance
“…Moreover, our method of lymph node dissection by clearing mesorectal fat significantly facilitated the detection of lymph node metastases. In the literature data, a reduced number of lymph node metastases after preoperative radiotherapy was reported in some studies 8,16,18,38,42,44 whereas in other studies no significant difference was found. 12,17,32 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, our method of lymph node dissection by clearing mesorectal fat significantly facilitated the detection of lymph node metastases. In the literature data, a reduced number of lymph node metastases after preoperative radiotherapy was reported in some studies 8,16,18,38,42,44 whereas in other studies no significant difference was found. 12,17,32 …”
Section: Discussionmentioning
confidence: 94%
“…In contrast to some studies, we did not observe a single case of complete tumor regression in patients with rectal carcinoma after preoperative radiotherapy. 7,30,38 This might be explained by the short delay between the end of the radiotherapy and surgery in the schedule used in the current study and also by the fact that only patients with locally advanced stages of rectal carcinoma were included in the current study compared with other studies in which a significant proportion of patients with cT1-T2 tumors was included. 30 To our knowledge, there have been no reports to date of complete tumor regression occurring when surgery is performed within 1 week after the end of radiotherapy, a finding that is consistent with our own data.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, radiotherapy alone or in combination with chemotherapy is used prior to surgery to reduce the tumor size. Extensive studies on the use of (chemo) radiotherapy for these tumors showed that preoperative radiotherapy decreases local recurrence rates by 50 to 60% as compared with surgery alone (43)(44)(45)(46)(47)(48)(49), and the addition of chemotherapy to radiotherapy has been shown to further increase local control (50)(51)(52)(53)(54). On the basis of these results, the current standard treatment of locally advanced rectal cancer consists of preoperative chemoradiation followed by total mesorectal excision surgery.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Although several trials, historically controlled or randomised (see the review by Cohen et al, 1989 andDahl et al, 1990), have found an improved local control after combined surgery and radiotherapy the actual importance, if any, of the sequence of the two treatment modalities remains to be investigated. Furthermore, in most of these trials the improvement in local control after preoperative radiotherpy did not result in any significant improvement in survival (Mayer et al, 1989;Cohen et al, 1989).…”
Section: Adjuvant Post-operative Radiotherapymentioning
confidence: 99%